2017
DOI: 10.1093/cid/cix512
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care β-Lactam Allergy Skin Testing by Antimicrobial Stewardship Programs: A Pragmatic Multicenter Prospective Evaluation

Abstract: The use of BLAST at the point of care across 3 hospital ASPs resulted in greater use of preferred β-lactam therapy without increasing the risk of adverse drug reactions. Longer-term studies are needed to better assess the safety and clinical impact of this ASP intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 13 publications
3
43
0
Order By: Relevance
“…Once risk is assessed, pathways will lead toward direct provocation challenges in low‐risk patients or skin testing in higher risk patients. One inpatient multi‐center ASP‐led beta‐lactam allergy testing service has already been shown to improve beta‐lactam usage . A multidisciplinary ASP‐led approach in Australia was able to remove a penicillin allergy label in 83% of patients and increase narrow‐spectrum beta‐lactam (aOR, 3.54; 95% CI, 1.98‐6.33) and appropriate antibiotic usage (aOR, 12.27; 95% CI, 5.00‐30.09) up to 90‐day post‐testing .…”
Section: Current Approaches To Penicillin Allergy Labels and Penicillmentioning
confidence: 99%
“…Once risk is assessed, pathways will lead toward direct provocation challenges in low‐risk patients or skin testing in higher risk patients. One inpatient multi‐center ASP‐led beta‐lactam allergy testing service has already been shown to improve beta‐lactam usage . A multidisciplinary ASP‐led approach in Australia was able to remove a penicillin allergy label in 83% of patients and increase narrow‐spectrum beta‐lactam (aOR, 3.54; 95% CI, 1.98‐6.33) and appropriate antibiotic usage (aOR, 12.27; 95% CI, 5.00‐30.09) up to 90‐day post‐testing .…”
Section: Current Approaches To Penicillin Allergy Labels and Penicillmentioning
confidence: 99%
“…allergy pathway conducted in Australia were led by infectious diseases physicians. 20,54 Pharmacist Pharmacists, particularly infectious diseases or ASP pharmacists, were instrumental to most beta-lactam allergy pathways. 32,33,37,38,[45][46][47] Pharmacists designed and led interventions.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…29 Two PST-based pathways reported that their approach saved approximately 50 doses of vancomycin. 39,41 Other PST-based pathways reported carbapenem and fluoroquinolone reduction (28% to 13%), 20 and aztreonam reduction (2.54 to 1.47 administrations per 1000 patient-days). 48 In the initial MGH pathway study, vancomycin, aztreonam, aminoglycosides, and fluoroquinolones were switched to beta-lactams using test doses.…”
Section: Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] This recommendation is based on the high negative predictive value of skin tests reported by American studies in which bencylpenicillin and penicillin V were predomi nantly prescribed. 18 However, more recent Eu ropean studies reported that between 8.4% and 30.7% of patients with negative results reacted to drug challenge.…”
mentioning
confidence: 99%